2012
DOI: 10.1590/s1415-47572012005000043
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel single nucleotide polymorphisms in the DGAT1 gene of buffaloes by PCR-SSCP

Abstract: Diacylglycerol O-acyltransferase 1 (DGAT1) is a microsomal enzyme that catalyzes the final step of triglyceride synthesis. The DGAT1 gene is a strong functional candidate for determining milk fat content in cattle. In this work, we used PCR-SSCP (polymerase chain reaction-single-strand conformation polymorphism) and DNA sequencing to examine polymorphism in the region spanning exon 7 to exon 9 of the DGAT1 gene in Murrah and Pandharpuri buffaloes. Three alleles (A, B and C) and four novel single-nucleotide pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
(22 reference statements)
2
10
0
Order By: Relevance
“…The allele variant A was the most frequent in all of the breed groups, and, consequently, the genotype AA was found at a high frequency in the Murrah and mixed-breed groups. Very similar results were obtained by Raut et al (2012) when studying Murrah and Pandharpuri buffaloes. Shi et al (2012) investigated Murrah buffaloes for the presence of SNPs between introns 7 and 8 of DGAT1, and detected a polymorphic point at position 256, which was observed in our study.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The allele variant A was the most frequent in all of the breed groups, and, consequently, the genotype AA was found at a high frequency in the Murrah and mixed-breed groups. Very similar results were obtained by Raut et al (2012) when studying Murrah and Pandharpuri buffaloes. Shi et al (2012) investigated Murrah buffaloes for the presence of SNPs between introns 7 and 8 of DGAT1, and detected a polymorphic point at position 256, which was observed in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Four patterns of bands were found for this gene, which were sequenced and compared with those described by Raut et al (2012) Four genotypes were observed in the Murrah breed and three were observed in the Mediterranean and mixed-breed groups (Table 1). Allele variant A was the most frequent variant in the Murrah, Mediterranean, and mixed-breed groups (0.79, 0.69, and 0.77, respectively) ( Table 1).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations